2014
DOI: 10.1016/j.ijcard.2013.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Clinical research priorities in adult congenital heart disease

Abstract: Background Adult congenital heart disease (ACHD) clinicians are hampered by the paucity of data to inform clinical decision-making. The objective of this study was to identify priorities for clinical research in ACHD. Methods A list of 45 research questions was developed by the Alliance for Adult Research in Congenital Cardiology (AARCC), compiled into a survey, and administered to ACHD providers. Patient input was sought via the Adult Congenital Heart Association at community meetings and online forums. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 147 publications
1
21
0
Order By: Relevance
“…Patients are starting to partner with investigators to identify research priorities that are relevant to their experience. 11 In some cases, patients and their advocacy groups are establishing their own research initiatives, recruiting patients into registries, designating centers of excellence, and educating regulatory agencies about how best to support their community's needs.…”
Section: Engaging Patientsmentioning
confidence: 99%
“…Patients are starting to partner with investigators to identify research priorities that are relevant to their experience. 11 In some cases, patients and their advocacy groups are establishing their own research initiatives, recruiting patients into registries, designating centers of excellence, and educating regulatory agencies about how best to support their community's needs.…”
Section: Engaging Patientsmentioning
confidence: 99%
“…On the basis of expert opinion and published research priorities in CHD (20,21), 3 broad high-impact areas were identified: HF; vascular disease; and multisystem complications. The first interest area involved understanding the pathophysiology of and optimizing management strategies for HF in CHD, a common problem that will continue to grow as the ACHD population ages.…”
Section: Working Groupmentioning
confidence: 99%
“…Over the past decade, significant progress has been made toward these goals (19-21), due to the support of advocacy groups and federal agencies, increased training of ACHD clinician-scientists, and volunteerism of professionals and societies. The Alliance for Adult Research in Congenital Cardiology (22), a research network of investigators from 15 centers, was created in 2006 (19).…”
mentioning
confidence: 99%
“…Cotts et al for the Alliance for Adult Research in Congenital Cardiology compiled a list of 45 questions and conducted a survey of providers to identify 10 priority questions, with some input from patient groups. [19] Of these, four were specific to patients with single ventricle heart conditions: ‘Is pulmonary vasodilator therapy beneficial in Fontan patients?’, ‘Are warfarin and/or aspirin beneficial in preventing primary thromboembolic events in adult Fontan patients?’, ‘What is the optimal medical therapy for preservation of ventricular systolic and diastolic function in Fontan patients?’ and ‘What is the optimal medical treatment algorithm for Fontan patients with protein-losing enteropathy (PLE)?’, whilst another was also relevant: ‘What are the ideal criteria for transplantation referral in ACHD?’. Similar questions to each of these were posed in our initial survey but only preservation of ventricular function was included as a priority.…”
Section: Discussionmentioning
confidence: 99%